Optimal topology for consensus using genetic algorithm - Mondal, Sabyasachi; Tsourdos, Antonios (Elsevier, 2020)
In the Multi-Agent Systems (MAS), graph network topologies play a crucial role in building consensus among the connected agents. Consensus may be achieved on many network graphs using distributed control theory. However, the optimal network topology is not addressed in most of the literature, which is an important part of building stable consensus among networked agents. In this paper, the optimal topology is obtained irrespective of the agent dynamics by using two-dimensional Genetic Algorithm (GA), which is a new approach in this context. Simulation result for agents with first, and second-order linear dynamic is obtained. These results show that the proposed method achieves consensus using the optimal network topology satisfactorily.
Keywords: Optimal topology; Two-dimensional Genetic Algorithm; Distributed control; Multi-Agent System (MAS); Consensus